2011
DOI: 10.1163/092050610x508400
|View full text |Cite
|
Sign up to set email alerts
|

Application of MS-Based Proteomics to Study Serum Protein Adsorption/Absorption and Complement C3 Activation on Poly(ethylene glycol) Hydrogels

Abstract: Although the interaction between cells and poly(ethylene glycol) (PEG) hydrogels is well documented, there lacks a thorough investigation into the adsorption of blood proteins on these surfaces which dictates the observed cellular and in vivo host response. Thus, a clear understanding of how surface-bound proteins mediate the unique biological property of PEG hydrogels is fundamentally important. The information obtained will also provide insights into future biomaterial design. In this study, several mass-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 47 publications
(39 reference statements)
6
31
0
Order By: Relevance
“…This trend was consistent with previous observations in our laboratory using a semi-interpenetrating network composed of physically entangled polyethylene glycol and gelatin macromolecules [25]. For the Mø monoculture gelatin/polyethylene glycol condition, temporal variations in the type, composition, and concentration of adsorbed protein can contribute to changes in macrophage phenotypic behavior causing lowered TNF-␣ expression observed at 4 days [26,27]. MSCs entrapped within gelatin/polyethylene glycol respond to potentially lethal TNF-␣ levels via a nuclear factor ␤ (NF-B) mechanism that causes several anti-inflammatory factors to be secreted (TNF-␣ stimulated gene-6 protein, interleukin-1 receptor antagonist, prostaglandin E2, and stanniocalcin-1) that downregulate TNF-␣ expression and direct adherent macrophages toward an M2 alternatively activated state [28 -30].…”
Section: Msc Biomatrix Downregulates Mø Proinflammatory Functionsupporting
confidence: 92%
“…This trend was consistent with previous observations in our laboratory using a semi-interpenetrating network composed of physically entangled polyethylene glycol and gelatin macromolecules [25]. For the Mø monoculture gelatin/polyethylene glycol condition, temporal variations in the type, composition, and concentration of adsorbed protein can contribute to changes in macrophage phenotypic behavior causing lowered TNF-␣ expression observed at 4 days [26,27]. MSCs entrapped within gelatin/polyethylene glycol respond to potentially lethal TNF-␣ levels via a nuclear factor ␤ (NF-B) mechanism that causes several anti-inflammatory factors to be secreted (TNF-␣ stimulated gene-6 protein, interleukin-1 receptor antagonist, prostaglandin E2, and stanniocalcin-1) that downregulate TNF-␣ expression and direct adherent macrophages toward an M2 alternatively activated state [28 -30].…”
Section: Msc Biomatrix Downregulates Mø Proinflammatory Functionsupporting
confidence: 92%
“…For example, PEG hydrogels are well known as resistant to protein adsorption; however, a study on the PEG-like surface tetraglyme indicated that complement protein C3 is the primary mediator of monocyte adhesion to tetraglyme [38]. Additionally, C3 activity on PEG hydrogels is comparable to TCPS, and monocyte adhesion to PEG hydrogels is lowered when using C3-depleted serum [24]. C3 is present only at very low, nearly undetectable levels in FBS, while adult humans have a C3 concentration of approximately 75-135 mg/dl [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the surface properties, biomaterials promote differential adsorption of certain serum proteins, and thus we hypothesized that the effect of serum type may vary by surface [1]. For example, polyethylene glycol (PEG) hydrogels limit adsorption of common serum proteins but may sustain significant complement component 3 (C3) activity comparable to other surfaces, potentially allowing this protein to take on a more influential role in mediating monocyte/macrophage responses [24]. FBS high abundance proteins include: bovine serum albumin (BSA), alpha-1-antiproteinase, plasminogen, lactoperoxidas, kniogen (LMW II), alpha-2-HS-glycoprotein, hemiferrin, prothrombin, apolipoprotein A-I, integrin beta-1, IGFBP2, IGF II, TGF-beta1 [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The collected monocytes were examined for purity using CD14-PE (AbD Serotec, Raleigh, NC) and CD45-FITC (BD Biosciences) monoclonal antibodies with appropriate fluorescence-minus-one and negative controls, which resulted in~80-90% monocyte purity with the contaminant being lymphocytes using flow cytometry characterization (24,25). Autologous human serum (AHS) was obtained from whole blood without sodium citrate as previously described (23,26).…”
Section: Cell Isolationmentioning
confidence: 99%